2020
DOI: 10.32360/acmar.v53i1.43330
|View full text |Cite
|
Sign up to set email alerts
|

A NORTHERN RECORD OF PANTROPICAL SPOTTED DOLPHINS (Stenella attenuata) IN SOUTHWEST ATLANTIC OCEAN

Abstract: Pantropical spotted dolphins, Stenella attenuata, are found across all tropical and subtropical oceans around the world, but their distribution is poorly known in the Southwestern Atlantic Ocean (SWA). A group of approximately 10 S. attenuata individuals was sighted in deep (~3,000 m), warm (~27.5 °C) and oligotrophic waters, near oceanic banks off northeastern Brazil (02°04’16.68” S and 038°08’28.26” W). This sighting constitute a new record of the northern distribution of S. attenuata in SWA. More survey eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Despite being widely distributed, the ecology of the species in the southwestern Atlantic Ocean (SWA) is not well known (e.g., Do Amaral et al, 2015;Moreno et al, 2005). Previous studies in the SWA indicated that the northern limit of its distribution is in oceanic tropical waters (02 04 0 S), whereas the southern limit is 22 42 0 S (Gurjão, 2020;Moreno et al, 2005). Most sightings have been documented at lower latitudes in association with tropical warm and deep waters (Di Tullio…”
mentioning
confidence: 99%
“…Despite being widely distributed, the ecology of the species in the southwestern Atlantic Ocean (SWA) is not well known (e.g., Do Amaral et al, 2015;Moreno et al, 2005). Previous studies in the SWA indicated that the northern limit of its distribution is in oceanic tropical waters (02 04 0 S), whereas the southern limit is 22 42 0 S (Gurjão, 2020;Moreno et al, 2005). Most sightings have been documented at lower latitudes in association with tropical warm and deep waters (Di Tullio…”
mentioning
confidence: 99%